The Roles of Village Headman of the Futue Headman - Supajaroonwong, Anaya (Arts of Management Journal, 2020)
The purposes of this study were (1) to study the factors influencing the desirable roles of local leaders in the future; and (2) to study the problems and obstacles pertaining to the desirable roles of local leaders. The sample was local leaders and other local government leaders. The instrument used was a purposive sampling technique. The instrument for collecting data was in-depth interviews. Analysis data were descriptive statistics and content analysis. The research results were found that the factors influencing the desirable roles of local leaders in the future will be 1) the factor concerns about the local leaders’ educational degree; 2) the respect to the governance and the law and order. The local leaders should have the ability to protect people’s lives and assets. The local leaders should also play a leading role in the promotion and development of occupations of the locals; and 3) in the role of environmental duty, local leaders should be responsible for the promotion and support the locals to take care of canals, rivers, forests and other natural resources. Also, they must strongly adhere to the strict discipline, the perseverance, dedication, devotion, and they must conduct their official business using the principle of good governance. The results of this research were found that the factors influencing the desirable roles of local leaders in the future will be education, knowledge and ability, governance and the law and order, promotion and development of occupations of the locals, as well as promote and support the locals to take care of canals, rivers, forests and other natural resources, and prevention of disaster.